Pengaruh Celebrity characteristic terhadap impulse buying melalui Celebrity endorsement dan Hedonic attitude serta Utilitarian attitude: Pendekatan Teori S-O-R - Karamoy, Rivalni Virginia; Masnita, Yolanda; Kurniawati, Kurniawati (J-MAS (Jurnal Manajemen dan Sains), 2024)
Impulse buying, is a consumer behavior characterized by spontaneous and unplanned buying decisions. The main problem faced in this research is how celebrity characteristics influence impulse buying through celebrity endorsement as well as hedonic attitude and utilitarian. This study used Structural Equation Modeling (SEM) to analyze data from 171 respondents to identify the relationship between these variables. The results show that celebrity characteristic has a significant positive effect on celebrity endorsement (coefficient 0.984, p-value 0.000), which then affects hedonic attitude (coefficient 0.757, p-value 0.000) and utilitarian (coefficient 0.686, p-value 0.000). Hedonic attitude increases impulse buying (coefficient 0.528, p-value 0.000), while utilitarian attitude has a negative influence (coefficient -0.296, p-value 0.005). The contribution of this study lies in an in-depth understanding of the role of celebrity characteristics in increasing the effectiveness of endorsements and their impact on impulse buying behavior. The conclusions of the study emphasize the importance of choosing the appropriate celebrity and designing marketing strategies that consider the emotional and rational aspects of consumers. Suggestions for marketers are to focus on relevant celebrity characteristics and integrate emotional and rational approaches in marketing campaigns to maximize the influence on impulse buying.